Analisis Daya Saing Komoditas Kedelai Menurut Agro Ekosistem: Kasus di Tiga Provinsi di Indonesia - Amar K. Zakaria; Wahyuning K. Sejati; Reni Kustiari (Jurnal Agro Ekonomi, 2010)
EnglishDomestic soybean production tended to fall from year to year. This is related to the low participation of farmers in soybean farm. This study aimed to obtain an objective picture about the profitability of soybean farming in three different agro-ecosystems, namely irrigated land, rain-fed lowland, and dry land. The analysis uses a matrix approach to policy analysis (PAM). Data obtained from the survey conducted in 2009 in three provinces, namely West Java, East Java and South Sulawesi. The research results showed that soybean farming in the three agro-ecosystems is quite efficient and competitive.  The competitive advantage analysis indicates that domestic produced soybean could be a substitute for imported soybean. Increased participation of farmers in soybean farming is constrained by the lack of availability of high yielding variety of seeds, farming risk is quite high, and there is no price guarantee for soybean product.IndonesianProduksi kedelai domestik cenderung turun dari tahun ke tahun. Hal ini terkait dengan rendahnya partisipasi petani dalam usahatani tanaman kedelai. Penelitian ini ditujukan untuk memperoleh gambaran objektif mengenai profitabilitas usahatani kedelai di tiga agroekosistem yang berbeda yaitu di lahan sawah irigasi, lahan sawah tadah hujan, dan lahan tegalan. Analisis menggunakan pendekatan matrik analisis kebijakan (PAM). Data diperoleh dari hasil survei pada Tahun 2009 di tiga provinsi yaitu Jawa Barat, Jawa Timur dan Sulawesi Selatan. Hasil analisis menunjukkan bahwa usahatani kedelai di tiga agrosistem tersebut cukup efisien dan keunggulan kompetitifnya cukup memadai sebagai substitusi impor. Peningkatan partisipasi petani dalam usahatani kedelai terkendala oleh kurang tersedianya benih unggul bermutu, risiko usahatani yang cukup tinggi, dan tidak adanya jaminan harga jual kedelai yang layak.